Using Small Peptide Segments of Amyloid-β and Humanin to Examine their Physical Interactions - Heyl, Deborah L.; Iwaniec, Brandon; Esckilsen, Daniel; Price, Deanna; Guttikonda, Prathyusha; Cooper, Jennifer; Lombardi, Julia; Milletti, Maria; Evans, Hedeel G. (Protein and Peptide Letters, 2019)
Background: Amyloid fibrils in Alzheimer’s disease are composed of amyloid-β (Aβ) peptides of variant lengths. Humanin (HN), a 24 amino acid residue neuroprotective peptide, is known to interact with the predominant Aβ isoform in the brain, Aβ (1-40). Methods: Here, we constructed smaller segments of Aβ and HN and identified residues in HN important for both HN-HN and HN-Aβ interactions. Peptides corresponding to amino acid residues 5- 15 of HN, HN (5-15), HN (5-15, L11S), where Leu11 was replaced with Ser, and residues 17-28 of Aβ, Aβ (17-28), were synthesized and tested for their ability to block formation of the complex between HN and Aβ (1-40). Results: Co-immunoprecipitation and binding kinetics showed that HN (5-15) was more efficient at blocking the complex between HN and Aβ (1-40) than either HN (5-15, L11S) or Aβ (17-28). Binding kinetics of these smaller peptides with either full-length HN or Aβ (1-40) showed that HN (5- 15) was able to bind either Aβ (1-40) or HN more efficiently than HN (5-15, L11S) or Aβ (17-28). Compared to full-length HN, however, HN (5-15) bound Aβ (1-40) with a weaker affinity suggesting that while HN (5-15) binds Aβ, other residues in the full length HN peptide are necessary for maximum interactions. Conclusion: L11 was more important for interactions with Aβ (1-40) than with HN. Aβ (17-28) was relatively ineffective at binding to either Aβ (1-40) or HN. Moreover, HN, and the smaller HN (5-15), HN (5-15 L11S), and Aβ (17-28) peptides, had different effects on regulating Aβ (1-40) aggregation kinetics.
Keywords: peptide